Adequacy and change in nutrient and food intakes with aging in a seven-year cohort study in elderly women - Zhu, K.; Devine, A.; Suleska, A.; Tan, C.; Toh, C.; Kerr, Deborah; Prince, R. (Springer, 2010)
Objective. As women age total dietary intake falls which may increase the risk of dietary deficiencies in some individuals. The aims of this study were to investigate the changes in nutrient and dietary intakes that occurred with aging in a seven-year longitudinal study of elderly Australian women and to evaluate the adequacy of their dietary intakes. Design. Longitudinal population based study on health with ageing. Participants and setting 911 free-living elderly women aged 70–85 years at baseline from a cohort of 1500 elderly women. Measurements at baseline, 60 and 84 months, self-reported Food Frequency Questionnaires (FFQ) and demographics were collected and anthropometry measured.Results. During the 84 month subjects lost height (1.8 cm) and body weight (1.9 kg). Intakes of energy and macronutrients carbohydrate, fat and protein declined significantly over the 84 months. Mean energy derived from saturated fat was above, whereas energy derived from carbohydrate was below, recommended levels of intake at all time points. Intakes of vitamins and minerals all declined with age and subjects had suboptimal intakes of folate, vitamin E and calcium at all time points. The serve sizes for potato and meat and the consumption of milk, bread and variety of vegetables declined significantly over time reflecting changes in nutrient intake. Conclusions. Ageing is associated with reduced food intake resulting in inadequate intakes in energy, and some nutrients. Nutrition policy for elderly women should include advice to maintain or increase intakes of carbohydrate, milk, vegetables and fruit whilst continuing to reduce fat intake.